Complex factors combinations driving tea growers to adopt ecological agricultural practices in tea gardens - Yan, Zhaoshuo; Zhang, Wenzhe; Liu, Xiao; Li, Zhengyuan; Zhao, Yutao; Zeng, Mingjiang (Frontiers in Ecology and Evolution, 2024)
IntroductionThe implementation of ecological agriculture practices in Chinese tea gardens plays a vital role in mitigating N2O emissions and addressing environmental degradation. Nevertheless, a dearth of discourse exists regarding the intricacies surrounding farmers' adoption of tea garden ecological agriculture practices (TGEAP), particularly the complex interplay between adoption factors and outcomes.MethodsUsing data of 310 farmers, this study employed complexity theories and Stimulus-Organism-Response theories, and integrated Partial Least Squares Structural Equation Modeling and fuzzy-set Qualitative Comparative Analysis to explore the complex relationships between farmer characteristics, internal and external factors, and adoption of farmer.ResultsThe results show three influential paths in the Stimulus-Organism-Response model, and environmental protection attitude (EPA) and production expectation (PE) act as intermediaries. Notably, EPA exhibits a masking effect in one pathway. These paths linked closely to three farmer characteristics. Beyond the Stimulus-Organism-Response model, nine combinations lead to farmers' adoption, and four to non-adoption.DiscussionWe discover scenarios where opposing environmental states or age lead to adoption, explaining the masking effect. These combinations highlight how a favorable environment influences both adoption and non-adoption. We also discuss other combinations that lead to adoption or non-adoption. The study suggests that governments employ targeted incentives to facilitate tea farmers' transition in agriculture.